Influence of Ultrasonic Activation on the Physicochemical Properties of Calcium Silicate-Based Cements - Fredson Márcio Acris De Carvalho; Yara Teresinha Corrêa Silva-Sousa; Carlos Eduardo Saraiva Miranda; Paulo Henrique Miller Calderon; Ana Flávia Simões Barbosa; Luciana Martins Domingues De Macedo; Fuad Jacob Abi Rached-Junior (Hindawi Limited, 2021)
Purpose. To evaluate the influence of ultrasonic activation on the physicochemical properties of setting time (ST), flow (FL), dimensional change (DC), and solubility (SL) of the cements: MTA, MTA Repair HP, and Biodentine®. Materials and Methods. Two experimental groups were formed according to the cement activation protocol: without ultrasonic activation and with ultrasonic activation. Cements were manipulated according to the manufacturers' instructions. Ultrasonic activation group was performed with an E1 insert at power 3 (24-32 kHz) for 30 s directly in the center of the cement mass. The molds for analysis of the physicochemical properties were filled out and evaluated according to specification No. 57 from ANSI/ADA. The results were analyzed using the ANOVA test (two-way), complemented by Tukey's test (α = 0.05). The distilled water used during the solubility test was submitted to spectrometry to verify the release of calcium ions. The morphologies of the external surface and the cross-section of the samples were analyzed by means of a scanning electron microscope (SEM). Results. For the ST, ultrasonic activation reduced the values of MTA, MTA Repair HP, and Biodentine (P<0.05). For the FL, ultrasonic activation did not alter the flow of MTA (P>0.05); however, it increased the flow MTA Repair HP and Biodentine (P<0.05). For the DC, the percentage values of dimensional change were higher when there was ultrasonic activation in all repair cements (P<0.05). For SL, there was a reduction in the percentage of the values in MTA and MTA Repair HP (P<0.05); however, there was no change in the values of Biodentine (P>0.05). Ultrasonic activation favored the release of calcium ions from all cements. The SEM analysis showed, in general, that the ultrasonic activation reduced and altered the particle shape of the cement. Conclusions. The ultrasonic activation interfered in the ST, DC, FL, ultrastructural morphology, and calcium release of the repair cements. However, it did not affect the solubility of Biodentine®.